“Classe C” na TV: imagens de uma mitologia brasileira - Ikeda, Flavia Suzue de Mesquita (2016)
The main objective of this dissertation is to investigate the construction of senses in televised images from the so-called “C class”, especially on Globo TV channel. That interests how, from the appropriation and denomination of a deprived sociological sense of class, the TV station has contributed and fixed images related to this audience. The study is guided by the concept of myth which is offered by Roland Barthes in his semiological analyses of discourse and mass culture. The mythical speech can understand writings or representations and all media that can suit as a support, as far as the naturalisation of ideologies and social practices are observed. Authors from different theoretical perspectives, who are relevant to this proposal, are investigated. Television is approached from its insertion in cultural industry, according to references from critical theory, bearing in mind its important role to the formation of a common repertoire towards different classes, areas and groups concerning a debate about reality. It is highlighted that television had developed itself linked to social, economic and political transformations that have influenced not only its technical evolution, but also its content and discourses. This dissertation involves a retrospective through moments of our television history, searching intersections between the content and televised outreach, plus increase, maintenance or transformation of consumer market at certain moments, based on authors such as Hamburger, Ortiz, Bucci and Motter, among others. We emphasize images formulated in fiction from patterns of collective consciousness about Brazilians. The interest is to reflect about the way such figures are activated in imagination about urban and regional outskirts, contributing to constructions related to this “C class”. Texts from Marcelo Neri that specifically deal with this “C class” and search to locate the group in terms of the “new middle class” are summoned to oppose authors such as Jessé Souza and Márcio Pochmann. At Globo, the symbolic recognition of the existence of this “new middle class” has been reflected in humorous, fictional and news programs. We consider the years of 2011 and 2012, when the “C class” theme at this TV station lined not only the press, but also arose researchers’ interest, those who were involved in television studies, mostly soap operas. For analysis, we scrutinize the soap opera called “Cheias de charme”, that had stood out in the time period mentioned above because of its formal and content elaboration related to the “Class C”, besides the recent ideas of modernization and social transformation